Koponenius gen. nov., a new genus of the millipede family Haplodesmidae from the Himalayas of India and Nepal (Diplopoda: Polydesmida) - Golovatch, Sergei I.; Vandenspiegel, Didier (Zootaxa, 2014)
The first, apparently westernmost indigenous representatives of Haplodesmidae are reported, from the Himalayas of Nepal and India. Both new species belong to a new genus, Koponenius gen. nov., with K. unicornis sp. nov., the type species from Darjeeling District, NE India, and K. biramus sp. nov., from Nepal. The new genus is superficially very similar to Prosopodesmus Silvestri, 1910, most species of which seem to be native to tropical Australia, partly also to southern Japan. However, Koponenius gen. nov. is easily distinguished in showing only 19 body segments, a special ozopore formula (5, 7–18), 4 transverse rows of setigerous isostictic tubercles per postcollum metatergum, and a clearly helicoid, twisted prefemoral portion of the gonopod so that the seminal groove runs mostly laterally, not mesally.